Epigenetic Mechanisms Affecting Macronuclear Development in Paramecium and Tetrahymena - PREER, JR, J. O. H. N R (The Journal of eukaryotic microbiology, 2000)
Epigenetic inheritance includes all non-Mendelian inheritance, in fact any inheritance that does not arise from base changes. Ciliates, particularly Paramecium and Tetrahymena, undergo epigenetic changes to their macronuclei when they are formed at nuclear reorganization. Once set, however, they are reproduced in a constant fashion, except for allelic segregations, during vegetative fissions in Tetrahymena and certain life cycle changes in both Paramecium and Tetrahymena. This review is meant to be inclusive, discussing all the known cases of epigenetic changes in macronuclei. They involve virtually all traits. We find that these macronuclear changes are subject to a variety of modifications in the way that they are implemented. They constitute a major feature of ciliate genetics, probably because the separation of generative and vegetative functions to micronuclei and macronuclei makes such changes possible.